2015
DOI: 10.1037/xhp0000103
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the psychological refractory period and prioritized processing paradigms: Can the response-selection bottleneck model explain them both?

Abstract: Four experiments examined whether well-established phenomena from the psychological refractory period (PRP) paradigm are also observed in the prioritized processing paradigm, as would be expected from a common description of the 2 paradigms with the response selection bottleneck (RSB) model. Consistent with a generalization of the RSB model to the prioritized processing paradigm, Experiments 1 and 2 showed that this paradigm yields effects of SOA and stimulus discriminability analogous to those observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 74 publications
(138 reference statements)
10
56
1
Order By: Relevance
“…In Experiment 1 of Miller and Durst (2014), participants gave both responses with either the left or the right index finger, and the fastest RT1s were observed in R1-R2 compatible trials, intermediate RT1s in R1-R2 incompatible trials, and the slowest RT1s if Task 2 was a no-go trial (even though none of these possible R2s actually had to be carried out). 1 The results revealed both an R1-R2 and a no-go BCE in this experiment, and similarly so in Experiments 1 and 2 of Miller and Durst (2015). In contrast, using different sets of effectors for both tasks, no R1-R2 BCE was reported in Miller and Durst's (2014) Experiment 2.…”
Section: A Closer Look At the No-go Bcesupporting
confidence: 65%
See 1 more Smart Citation
“…In Experiment 1 of Miller and Durst (2014), participants gave both responses with either the left or the right index finger, and the fastest RT1s were observed in R1-R2 compatible trials, intermediate RT1s in R1-R2 incompatible trials, and the slowest RT1s if Task 2 was a no-go trial (even though none of these possible R2s actually had to be carried out). 1 The results revealed both an R1-R2 and a no-go BCE in this experiment, and similarly so in Experiments 1 and 2 of Miller and Durst (2015). In contrast, using different sets of effectors for both tasks, no R1-R2 BCE was reported in Miller and Durst's (2014) Experiment 2.…”
Section: A Closer Look At the No-go Bcesupporting
confidence: 65%
“…Thus, on each trial, only one response is required, and clear priority is given to Task 1, since S2 need not even be considered if Task 1 is a go trial. In many respects, the performance patterns in the PP paradigm are reconcilable with the bottleneck model used to explain the PRP effect (see, in particular, Miller & Durst, 2015).…”
Section: A Closer Look At the No-go Bcementioning
confidence: 88%
“…Closer relatives to our own design are dual-task studies (with two distinct stimuli for each task) involving a go/nogo task as Task 2. For example, Miller (2006) showed that trials involving a no-go stimulus (vs. a go stimulus) in Task 2 were characterized by a Task 1 RT increase (see also Janczyk & Huestegge, 2017;Miller & Durst, 2014, 2015. It was assumed that this effect is based on an inhibitory response triggered by the no-go stimulus, which (either directly or via its transformation into a dedicated Binhibitory response^selection process) eventually prolongs Task 1 processing (see Röttger & Haider, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Task 1 response times (RTs) were shorter when Task 2 required a response relative to when it did not. This no-go backward crosstalk effect (no-go BCE) is an example of how dual-task costs are actually reduced when two motor tasks have to be carried out (see also Ko & Miller, 2014;Miller & Durst, 2014, 2015, even though the addition of a second task certainly impedes performance of the first task overall (i.e., general dual-task costs are present).…”
mentioning
confidence: 99%